Variation in resource use between adult and juvenile Semipalmated Sandpipers (Calidris pusilla) and use of physiological indicators for movement decisions highlights the importance of small staging sites during southbound migration in Atlantic Canada - Linhart, Rebeca C.; Hamilton, Diana J.; Paquet, Julie; Bellefontaine, Sara C.; Davis, Siena; Doiron, Parker B.; Gratto-Trevor, Cheri L. (Frontiers in Ecology and Evolution, 2022)
Semipalmated Sandpipers (Calidris pusilla) are Arctic-breeding shorebirds that use staging sites in Atlantic Canada during their annual migration to South America. The Bay of Fundy has long been recognized as a critical staging site for migrating Semipalmated Sandpipers and supports a large prey base. The diet of adult sandpipers in the Bay is flexible but the diet of juveniles, which arrive later, is not well documented. Comparatively little is known about the prey base and how it is utilized by sandpipers at sites in Atlantic Canada outside the Bay. Plasma metabolite measures can provide useful insight to assess habitat quality for sandpipers and have not yet been measured in Semipalmated Sandpipers in Atlantic Canada. To address these knowledge gaps we sampled shorebird habitat to estimate invertebrate availability in the Bay of Fundy and the Northumberland Strait. Concurrently, we collected blood samples from adult and juvenile sandpipers for analysis of plasma metabolite levels and isotopic estimates of dietary niche in both regions. We found that sites on the Northumberland Strait hosted a more diverse and variable prey base than sites within the Bay of Fundy, and that sandpipers were selective when foraging there, appearing to prefer bivalves. Juveniles may occupy a broader dietary niche than adults along the Northumberland Strait, though appear to gain weight as efficiently. Sandpipers sampled along the Northumberland Strait had higher plasma triglyceride concentrations than those within the Bay of Fundy, which may suggest differences in fattening rate or dietary fat intake. Sandpipers that had lower triglyceride concentrations on the Northumberland Strait were more likely to move into the Bay of Fundy, while sandpipers with high triglyceride values tended to remain on the Strait. These data suggest that sandpipers made movement decisions within the region depending on their physiological state. Our results suggest adult and juvenile Semipalmated Sandpipers successfully use a variety of staging habitats in Atlantic Canada. This is an encouraging finding for sandpiper conservation in the region, but also indicates that maintaining access to a broad variety of staging habitats is critical, supporting calls for stronger conservation measures throughout the region.